2020
DOI: 10.1002/aqc.3359
|View full text |Cite
|
Sign up to set email alerts
|

Exploring overlooked components of remote South‐east Pacific oceanic islands: Larval and macrobenthic assemblages in reef habitats with distinct underwater soundscapes

Abstract: 1. Identifying the diverse assemblage of species inhabiting rocky and coral reef habitats in isolated oceanic environments, and the important sound cues emitted from the reef, are crucial components to understand how species locate suitable habitats for the completion of their life-cycle and, thus, the functioning of these vulnerable ecosystems. 2. Recent field information suggests that the majority of reef biodiversity comprises small cryptic invertebrates; however, knowledge on these small components is extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Recent studies using metabarcoding of reef fish stomach contents have revealed elevated contributions of crustaceans (brachyuran and caridea), annellids, and fish larvae in their diets (Casey et al, 2019). In this study, brachyuran, caridean larvae, and nereid polychaetes, were important components of the emergent zooplankton assemblage (see Carrasco et al, 2020), with mixing models indicating distinct contributions from different sources of organic matter (macroalgae and coral mainly; Figure 5), emphasizing the potential trophic role of cryptofaunal adults and larval stages transferring OM through coral reefs (Kramer et al, 2013).…”
Section: Organic Matter Transference Mechanismsmentioning
confidence: 72%
See 2 more Smart Citations
“…Recent studies using metabarcoding of reef fish stomach contents have revealed elevated contributions of crustaceans (brachyuran and caridea), annellids, and fish larvae in their diets (Casey et al, 2019). In this study, brachyuran, caridean larvae, and nereid polychaetes, were important components of the emergent zooplankton assemblage (see Carrasco et al, 2020), with mixing models indicating distinct contributions from different sources of organic matter (macroalgae and coral mainly; Figure 5), emphasizing the potential trophic role of cryptofaunal adults and larval stages transferring OM through coral reefs (Kramer et al, 2013).…”
Section: Organic Matter Transference Mechanismsmentioning
confidence: 72%
“…mainly early life stages of benthic reef fauna) were sampled by deploying two light traps between 15 and 20 m depth and moored at 1-2 m from the reef bottom (Table 1). In all cases, traps were positioned to sample during one night and estimated to attract specimens from approximately 21:00 to 09:00 h; see Carrasco, Vandecasteele, Rivadeneira, Fernández, & Pérez-Matus, 2017;Carrasco et al, 2020).…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond fish sounds, PAM captures the whole soundscape (i.e., ambient sound). As such, it can also be used to monitor the cryptobiome [27,28] or to measure noise pollution [29]. In comparison with diver-based methods, PAM is cost-effective and can be deployed in a wide variety of situations.…”
Section: Introductionmentioning
confidence: 99%